A Solution Study of Complex Formation of Some Diamines with Lanthanones - J. J. Vora; D. R. Patel; Asha D. Patel; Kanu Patel; Sangita Sharma; Laxman S. Bhutadiya; Sunil B. Vasava (E-Journal of Chemistry)
To study the metal ligand equilibrium in aqueous solution, the well known Irving-Rossotti titration method was used. The temperature selected is 30±0.10C at ionic strength 0.2 M (NaClO4) which was maintained constant through out the work. The binary metal complex (ML2) formation was studied. The metals selected are Sm3+, Gd3+, Dy3+ and Yb3+. The diamine ligands taken are ethylenediamine, 1,2 diamino propane, 1,3 diamino propane, N-N diethyl ethylenediamine and N-N -dimethyl ethylenediamine. Factors that affected the stability of the complexes are size and ionic potential of lanthanone ions, basicity of ligands, ring size and steric effect of ligands.